New species of Gregorioiscala and Opalia (Caenogastropoda: Epitoniidae) in the Western Atlantic: a case of republication - Lima, Silvio Felipe Barbosa; Christoffersen, Martin Lindsey (Zootaxa, 2014)
In 2012, a report on ten gastropods of the family EPITONIIDAE Berry, 1910 collected from the deep sea off northeastern Brazil (2000-2001) was published in the International Journal of Zoology (IJZ). Two species were described as new to science (Lima et al. 2012). In August 2013, Dr. Philippe Bouchet (Muséum National d’Histoire Naturelle, Paris) brought to our attention the non-compliance of the IJZ—which is published exclusively as an online journal—with the requirements of the International Code of Zoological Nomenclature. Under the revised Article 8, the Code now allows electronic publication of new taxa published after 2011 under certain conditions: (1) the work has to be registered in ZooBank before it is published, and the work itself must contain evidence that registration has occurred; (2) the ZooBank registration must also state the name of an electronic archive intended to preserve the work and the ISSN or ISBN associated with the work (ICZN 2012). Neither of these requirements are met by the IJZ, and the previous descriptions of Gregorioiscala pimentai and Opalia revizee are thus unavailable under the Code. These epitoniids were dredged from the bathyal region off the state of Alagoas and are described herein based on conchological features. There are no similar congeners along the Brazilian coast.